Ayat-ayat Terkait Liberalisme dalam Al-Qur’an - Abdurrofi Muhammad Zainuri; Ahmad Zaki Yamini; Ahmad Nurali Shadiqin; Dinda Hidayatul; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
The maudu’i method of interpretation, which involves the presentation of the verse, its translation, asbabun nuzul, munasabah, and exegesis, is used in this study to investigate Islam and liberalism, one of the contemporaray issues, from a Qur’anic perspective. Starting with the Qur’anic term closest to the word “liberalism”, the maudu’I tafsir approach is used to quote and explain. The study comes to the conclusion that liberalism is freedom of thught from the perspevtive of Islam dand the Qur’an. The Arabic word for liberalism is muhararran which means pure. Thus the Islamic reform movement, characterized by the introduction of Western subject with Wstern themes, is where the issues of liberalism in Islam first emerged. Moreover, Islamic liberalism aims to combine western-style higher education with Islamic beliefs.